Implementasi Program Tahfidz al-Qur’an terhadap Peningkatan Spiritual Siswa MAN 2 Kota Malang - Marwah, Rosedah Sa’datul; Hamid, Abdulloh; Tamwifi, Irfan; Af’idah R, Alfiana; Amelia A, Ayu Nilna (QUALITY, 2023)
Implementation of the Tahfidz al-Qur'an Program for Spiritual Improvement of Students of MAN 2 Malang City.The Tahfidz Al-Qur'an program has become an integral part of religious education in Islamic educational institutions. The main objective of this program is to assist students in memorizing and understanding the content of the Qur'an. Its impact is not only cognitive but also serves as an effort to enhance the students' spiritual aspect. This research aims to explore the implementation of the Tahfidz Al-Qur'an program in improving the spiritual development of students at MAN 2 Kota Malang. The research problem formulated in this study is how the implementation of the Tahfidz program can enhance students' spirituality. Furthermore, this issue is motivated by the phenomenon of moral degradation among teenagers today. Considering that MAN students are vulnerable to various influences from the external environment.This study adopts a qualitative research approach with a phenomenological perspective. The researcher analyzes the data through observation, documentation, and literature study. The research findings indicate that the Tahfidz Al-Qur'an program has several positive impacts on improving the spiritual development of students at MAN 2 Kota Malang. Through memorizing the sacred verses of the Qur'an, it strengthens the spiritual bond with Allah SWT, develops positive characteristics, and enhances strong spiritual values within the students. The implication of this research is that Islamic educational institutions need to design a well-integrated Tahfidz Al-Qur'an program, provide strong guidance, and create an environment that supports the spiritual growth of students. Program tahfidz Al-Qur'an menjadi bagian penting dari pendidikan keagamaan di lembaga pendidikan Islam. Tujuan utama program ini adalah untuk membantu siswa menghafal dan memahami isi Al-Qur'an, dampaknya tidak hanya dari aspek kognitif melainkan sebagai upaya meningkatkan aspek spiritual siswa juga. Penelitian ini bertujuan untuk mengeksplorasi implementasi program tahfidz Al-Qur'an terhadap peningkatan spiritual siswa MAN 2 Kota Malang. Rumusan masalah dalam penelitian ini yaitu bagaimana pelaksanaan program tahfidz dapat meningkatkan spiritual siswa. Terlebih lagi hal tersebut dilatarbelakangi oleh fenomena degradasi moral yang terjadi pada anak remaja saat ini. Mengingat bahwa siswa MAN adalah siswa remaja yang rentan dengan berbagai macam pengaruh dari lingkungan luar sekolah.Penelitian ini menggunakan penelitian kualitatif dengan pendekatan fenomenologi. Peneliti melakukan analisis data dengan observasi, dokumentasi, dan studi literatur. Temuan penelitian menunjukkan bahwa program tahfidz Al-Qur'an memberikan beberapa dampak positif terhadap peningkatan spiritual siswa di MAN 2 Kota Malang. Melalui penghafalan ayat suci Al-Qur’an memperkuat ikatan spiritual dengan pendekatan rohani kepada Allah SWT, mengembangkan sifat positif, dan meningkatkan nilai-nilai spiritual yang kuat dalam diri siswa. Implikasi dari penelitian ini, bahwa lembaga pendidikan Islam perlu merancang program tahfidz Al-Qur'an yang terintegrasi dengan baik, memberikan bimbingan yang kuat, dan menciptakan lingkungan yang mendukung pertumbuhan spiritual siswa.